A qualitative study investigating training requirements of nurses working with people with dementia in nursing homes. (March 2017) - Smythe, Analisa; Jenkins, Catharine; Galant-Miecznikowska, Magdalena; Bentham, Peter; Oyebode, Jan
Abstract: Background: The care home workforce (over half a million people in the UK) has a pivotal role in the quality of care provided to the residents. Much care in this setting is inadequate, lacks a person-centred focus and neglects the dignity of residents. A combination of factors leads to burnout in nurses working in nursing homes, contributing to poor quality care. Recent reports have indicated that cultures of care need to be addressed through training, improved workforce support and supervision and that improving the quality of care for people with dementia can be achieved by the development of leadership in nursing and clarifying professional values. Addressing burnout through an educational intervention should improve quality of care and nurses' experiences. Objectives: The study aimed to explore the training needs of nurses working with people with dementia in nursing homes with a view to developing an educational intervention to reduce nurses' burnout and improve person-centred care. Design: Four focus groups were conducted with 11 qualified nurses working in nursing homes; data was analysed using thematic analysis. Results: Four themes emerged through the analysis of the transcripts. Participants reported that their work responsibilities revolved mainly around directing others, day to day care, paper work and supporting family carers. Nurses identified the importance of person-centred ways of being, communication and clinical skills when working in nursing home setting. They expressed their frustrations associated with managing staff levels, responding to behaviour that challenges and lack of time. Conclusions: The barriers to learning, experience of previous training and gaps in knowledge identified could inform the design of future training and support programmes. Highlights: Focus groups were conducted with nurses working in nursing homes with people with dementia Effective approaches for future training were explored For training to be effective it should incorporate interactive practical sessions with relevant content